Efektivitas Intervensi Pendidikan Kesehatan Terhadap Tingkat Pengetahuan Dan Sikap Tentang Pemilahan Sampah Pada Siswa Sekolah Dasar Negeri Di Kota Serang Tahun 2015 - erna sariana (ARKESMAS [Arsip Kesehatan Masyarakat], 2018)
Rubbish sorting is to separate waste types in according to the dissociation nature. In Serang city, especially the State Elementary School in working area Puskesmas Taktakan as being the location TPSA Cilowong Serang City government property still carry out the separation of biodegradable garbage and is not readily biodegradable. This is related with the knowledge and attitudes about less waste sorting. The purpose of this study was to determine the effect of health education on the knowledge level and attitudes about the waste sorting at the State Elementary School students in the Serang City 2015. The method used is a quasi-experimental. Samples some students at class V SDN Serang City. The first group is the experimental sample is SDN Pereng Cilowong village, and the second group is the experimental sample was SDN Taktakan 1 Serang. Data was analyzed using univariate and bivariate analysis with dependent t test, independent t test, and the correlation test. Based on the research results revealed that the mean of knowledge before the health education intervention = 11.088, mean knowledge after = 12.431. Mean attitude before = 37.363, and the attitude of health education interventions after the mean values ​​obtained 38.902. No statistically significant difference between the average knowledge before and after the health education intervention in the experimental first group (p = 0.0001) and second group (p = 0.0001). There are significant differences between the average attitude before and after the health education intervention in the experimental first group (p = 0.002) and second group (p = 0.040). The score average students knowledge and attitude who are given health education interventions through the film, is higher than the students knowledge and attitudes who are given health education interventions through leaflets (p = 0.015 and p = 0.048). There is a significant relationship between knowledge and attitude about waste separation (r= 0.524) and p = 0.0001). Suggestions in this research is to be able to select and use the appropriate health education media for students, especially elementary school students who turned out to be more effective to use audio visual media be compared visual media. Keywords : Health Education, Knowledge, Attitude, Sorting Waste, Elementary School Students.